Mind the gap: Towards performance measurement beyond a plan-execute logic - Maylor, Harvey; Geraldi, Joana; Budzier, Alexander; Turner, Neil; Johnson, Mark (Elsevier, 2023)
Project performance measurement aims to identify deviations from intended goals and reduce ‘the gap’ between actual and expected performance. However, despite extensive measurement and control efforts, the gap is hard to close and, intriguingly, not necessarily related to the project's perceived performance, which is what will ultimately influence a stakeholder's satisfaction. Based on service quality research, this study explores the differences between perception and expectations of performance. Our mixed method study involving eighteen interviews and 85 survey responses in an IT-enabled change context shows that expectations and perceptions are fundamentally different concepts. As they are different, managing the gap between expectations and perceptions may be a nugatory task. The paper expands the literature on project performance measurement by questioning its foundations and offering a first step towards developing a more dynamic and subjective understanding of project performance that is consistent with a project's evolving nature.
Keywords: Project success; transformation projects; performance; SERVQUAL; project performance measurement; subjective performance